ANALISIS PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA DOSEN STIMI BANJARMASIN MELALUI ANALISIS SEM-PLS WARP PLS 3.0 - Mahfuzil Anwar (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2018)
Abstract, Organizational culture is usually always applied by an institution is a matter that continues to be done in a sustainable both in terms of departmentalization and division of labor. In carrying out its activities STIMI adheres to an organization, which means it is a functional institution or group. For every organization the process of organizing is an effort to determine the work to be done to achieve organizational goals, the proper division of labor, and the establishment of mechanisms to coordinate activities and skills in the functions within the organization. From the organizing function appears an organizational structure that shows the flow of interaction within the organizationi. Based on the description of the background of the problem, then the formulation of the proposed problem is: Is there any influence of Organizational Culture on Lecturer Performance at STIMI Banjarmasin. Research purposes to know the influence of Organizational Culture to Lecturer Performance at STIMI Banjamasin. Research Benefits: a) Research is expected to contribute thoughts or inputs STIMI Banjarmasin to taking a policy to improve Lecturer's performance. b) See how the theory of the research findings are expected to guide and serve the repertoire of literature in improving the performance of lecturers based on their organizational culture.